2013
DOI: 10.19056/ijmdsjssmes/2013/v2i2/86779
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphological Patterns in the Diagnosis of Tuberculous Lymphadenitis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…In the present study, the most common cytomorphological pattern observed on FNAC was that of well-formed epithelioid cell granulomas with caseous necrosis (34%). This was in agreement with the studies done by Laishram et al, 11 Shirish et al, 12 Khanna et al, 13 Thakur et al, 14 Mitra et al, 15 and Naaz et al, 16 Most cases of tubercular lymphadenopathy were observed to occur between 20-59 years of age in the present study, this was comparable with the study by Muluye et al, 17 who documented 54.6% cases in the adult age group (25-60 years) while Singh et al, 18 observed that the maximum number of the patients were between 20-40 years. Similar observations were made by Gupta et al, 4 and Jasim et al 19 Out of the total of 330 cases, females were more frequently diagnosed as suffering from tubercular lymphadenopathy (189 cases,57.3% of all).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the most common cytomorphological pattern observed on FNAC was that of well-formed epithelioid cell granulomas with caseous necrosis (34%). This was in agreement with the studies done by Laishram et al, 11 Shirish et al, 12 Khanna et al, 13 Thakur et al, 14 Mitra et al, 15 and Naaz et al, 16 Most cases of tubercular lymphadenopathy were observed to occur between 20-59 years of age in the present study, this was comparable with the study by Muluye et al, 17 who documented 54.6% cases in the adult age group (25-60 years) while Singh et al, 18 observed that the maximum number of the patients were between 20-40 years. Similar observations were made by Gupta et al, 4 and Jasim et al 19 Out of the total of 330 cases, females were more frequently diagnosed as suffering from tubercular lymphadenopathy (189 cases,57.3% of all).…”
Section: Discussionsupporting
confidence: 93%
“…The commonest pattern in this study was pattern B (66.34% cases) showing epithelioid granuloma with necrosis. The same was observed by Bhattacharya et al[18] and Khanna et al[19] in 69.4% and 50.5% cases, respectively.Results similar to our study were also demonstrated in the studies by Sulakshana et al[21], Ahmed et al[22], Abdelsadek et al[23], Mugulkod et al[15], and Stevanovic et al[3]. This was in contrast to the findings of Conde et al[22].…”
supporting
confidence: 87%
“…The most common cytomorphological pattern observed in our study was epithelioid granuloma with necrosis, seen in 53.17% cases. This was also the commonest pattern in the study by Khanna A et al, Bhattacharya S et al and Prasoon D et al [14][15][16] They reported this pattern in 50.5%, 69.4% and 44.2% of cases respectively. The presence of caseous necrosis without epithelioid granuloma was the least common pattern in our study, seen in 8.73% cases.…”
Section: Discussionmentioning
confidence: 59%